Humanism: essays on race, religion and cultural production - Pinn, Anthony B. (Bloomsbury, 2015)
Provides a much-needed humanities-based analysis and description of humanism in relation to theses cultural markers. Whereas most existing analysis attempts to explain humanism through the natural and social sciences (the "what" of life), Anthony B. Pinn explores humanism in relation to "how" life is arranged, socialized, ritualized, and framed. This ground-breaking publication brings together old and new essays on a wide range of topics and themes, from the African-American experience, to the development of humanist churches, and the lyrics of Jay-Z--